Quality Certificates Alleviate Consumer Aversion to Sponsored Search Advertising - Xiang Hui; Meng Liu (Center for Economic Studies and ifo Institute (CESifo), 2022)
We study consumer response towards sponsored search advertising and how to improve advertising performance on a large e-commerce platform. Our research design is based on a field experiment which randomizes the salience of ad disclosure to consumers, and a natural experiment which eradicates a listing-level quality certificate for all listings because of a system glitch. Results suggest that consumers dislike search advertising in our setting, but quality certificates mitigate this aversion and increase advertising sales.
Keywords: 330; sponsored search advertising; quality certificates; e-commerce